Micronized purified flavonoid fraction in the treatment of hemorrhoidal disease - Philippe Godeberge (2022)
Hemorrhoidal disease (HD) is common in adults. Treatment is largely conservative, although more invasive procedures may be required. Venoactive drugs such as micronized purified flavonoid fraction (MPFF) are widely used, but a recent and comprehensive review of supporting evidence is lacking. In acute HD, MPFF can reduce HD symptoms such as bleeding, pain, anal discomfort, anal discharge and pruritus. In patients undergoing surgery, postoperative adjunct MPFF consistently reduces pain, bleeding duration and use of analgesia. MPFF treatment is appropriate and effective both as a first-line conservative treatment and as a postoperative adjunct treatment. MPFF reduces the duration of hospital stay following surgery, facilitating a return to normal activity and improving quality of life. MPFF may also prevent HD recurrence.